Acute Hemolytic Transfusion Reaction in Group B Recipient Associated with Group A Apheresis Platelet Donor: Case Report and Literature Review - Tracy R. Shachner; Christopher T. Clark (Case Reports in Medicine)
Acute hemolytic transfusion reaction is a known but rare potential adverse event related to platelet transfusion. Most reported cases of platelet-related hemolytic transfusion reaction have resulted from transfusion of platelets from group O donor to group A recipient. We identified only one prior case report in the literature of hemolytic transfusion reactions resulting from transfusion of apheresis platelets from group A donor to group B recipient. In that case report, two platelet units were obtained from a single donation and transfused into two separate patients. Both patients exhibited acute hemolytic reactions. The donor is reported to have high anti-B titers, as well as report of probiotic use. We report a case of acute hemolytic reaction in group B recipient following transfusion of apheresis platelets from group A donor with high-titer anti-B but unknown status of probiotic use. This case demonstrates that while low, there still exists potential risk for hemolysis from out-of-group A plasma transfusion.